Trends in the development of information technology and the impact of artificial intelligence on the economy and business: Trends in the development of information technology and the impact of artificial intelligence on the economy and business - Muxiddinov, Davron (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Annotation: This article examines the latest trends in information technology development and their profound impact on the economy and business through the integration of artificial intelligence (AI). It explores how technologies such as cloud computing, 5G, IoT, cybersecurity, and blockchain are reshaping industries by enhancing connectivity, security, and efficiency. The article delves into AI's role in automating routine tasks, driving data-driven decision-making, personalizing customer experiences, and transforming financial services. It also addresses